Korelasi antara Paham Teologi tentang Perbuatan Manusia dengan Etos Belajar Mahasiswa STAIN Jember: The Correlation between Theological Understanding of Human Actions and the Learning Ethos of Students at the State Islamic College (STAIN) Jember - Kasman Kasman (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2004)
The low learning ethic among students at Islamic higher education institutions, most of whom adhere to Asy'ariyah theology, is a crucial issue in this study. This research departs from the classical Islamic theological problem of determinism versus human freedom, represented by the Jabariyah and Qadariyah schools, which, in theory, influence individual attitudes and behaviors, including learning ethic. The study aimed to examine the correlation between the theology of human activity and the learning ethic of STAIN Jember students and to measure the degree of that correlation. The research employed a survey approach with an explanatory design. Data were collected through questionnaires from 100 respondents using proportional stratified random sampling and were analyzed using the Chi-Square and Contingency Coefficient formulas. The results showed that there is a correlation between the theology of human activity and students' learning ethic, but at a low level (CC=0.32). Other important findings revealed no correlation between theological understanding and learning views, but a weak correlation with learning attitudes. It is concluded that theological understanding is not the dominant factor influencing learning ethic; thus, further research is recommended to identify other factors, such as curriculum, environmental conditions, and students' economic situations. Fenomena rendahnya etos belajar mahasiswa perguruan tinggi agama Islam yang mayoritas menganut paham teologi Asy’ariyah menjadi isu krusial dalam penelitian ini. Penelitian ini bertolak dari peta masalah teologis klasik dalam Islam mengenai determinisme versus kebebasan manusia yang diwakili oleh paham Jabariyah dan Qadariyah, yang secara teoritik memengaruhi sikap dan perilaku individu termasuk etos belajar. Tujuan penelitian adalah menguji korelasi antara paham teologi tentang perbuatan manusia dengan etos belajar mahasiswa STAIN Jember serta mengukur derajat korelasinya. Penelitian menggunakan pendekatan survei dengan desain eksplanatif. Data dikumpulkan melalui kuesioner dari 100 responden dengan teknik proportional stratified random sampling, dianalisis menggunakan rumus Chi-Square dan Koefisien Kontingensi. Hasil penelitian menunjukkan bahwa terdapat korelasi antara paham teologi tentang perbuatan manusia dengan etos belajar mahasiswa, tetapi pada tingkat hubungan yang lemah (KK=0,32). Temuan penting lainnya adalah tidak ada korelasi antara paham teologi dengan pandangan belajar, namun ada korelasi lemah dengan sikap belajar. Kesimpulannya, paham teologi bukan faktor dominan yang mempengaruhi etos belajar, sehingga direkomendasikan penelitian lebih lanjut untuk mengidentifikasi faktor-faktor lain seperti kurikulum, lingkungan, dan kondisi ekonomi mahasiswa.